An initial exploration of core collection construction and DNA fingerprinting in Elymus sibiricus L. using SNP markers - Li, Xinrui; Song, Daping; Li, Mingfeng; Li, Daxu; You, Minghong; Peng, Yan; Yan, Jiajun; Bai, Shiqie (Frontiers in Plant Science, 2025)
Elymus sibiricus L., an excellent forage and ecological restoration grass, plays a key role in grassland ecological construction and the sustainable development of animal husbandry. In China, the wild germplasm resources of E. sibiricus are abundant, and they are shaped by similar and contrasting climatic conditions to form distinct populations, which enrich the genetic diversity of E. sibiricus. To more comprehensively aggregate E. sibiricus germplasm resources at a lower cost and to more accurately utilize its genetic variation, this study conducted a preliminary exploration of core germplasm collections and fingerprinting of E. sibiricus using single nucleotide polymorphism (SNP) markers. By combining multiple evaluation measures with weighted processing, we successfully identified 36 materials from 90 wild E. sibiricus samples to serve as a core collection. Genetic diversity assessments, allele evaluations, and principal component analyses of the 36 core germplasm samples all indicate that these 36 samples accurately and comprehensively represent the genetic diversity of all 90 E. sibiricus germplasm accessions. Additionally, we identified 290 SNP loci from among the high-quality SNP loci generated by whole-genome sequencing of the 90 E. sibiricus samples as candidate markers. Of these, 52 SNP loci were selected as core markers for DNA fingerprinting of E. sibiricus. Using kompetitive allele-specific PCR (KASP) technology, we also performed population origin identification for 60 wild E. sibiricus germplasm accessions based on these core markers. The core SNP markers screened in this study were able to accurately distinguish between E. sibiricus germplasms from the Qinghai–Tibet Plateau and those from elsewhere. This study not only provides a reference for the continued collection and identification of E. sibiricus germplasm resources but also offers a scientific basis for their conservation and utilization.